The Effect Of Song Mnemonic On Students’ Vocabularymastery Of MTsN Tanjungbalai - Octaviani Octaviani (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
The objective of this research to identify the faced by the seventh grade students’ at MTsN Tanjung Balai, to identify the causes of students' difficulties in improving vocabulary mastery of seventh grade students at MTsN Tanjung Balai in the 2023/2024 academic year. The population was 54 students and the researcher took a 2 class random sampling design, namely: control class and experimental class to carry out pre-test post-test. Material about describing something. In collecting data, researchers used tests to apply the song mnemonic method for several weeks and compared the pre-test and post-test to determine the effect of applying the song mnemonic method. Then the data obtained was analyzed through five stages, namely normality test, homogeneity test, hypothesis test, effect size test and statistical hypothesis. Finally the researcher found that it showed that the value of the T-test was 7.659 and the degree of freedom (df) was 54 (df-2;54-2=52). The value of T is significant 5% of T-table of db= 2.00. Therefore, the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. It can be concluded that the influence of using the song mnemonic method has an influence on increasing students' mastery of English vocabulary. So the suggestion is that teachers must be more creative in developing appropriate learning methods to be taught to support effective learning activities in the classroom.